Dari Sastra Anak ke Pendidikan Akidah-Akhlak: Analisis Naratif Terhadap Novel Petualangan Si Bocah Soleh - Al-Muta'aliyah, Fayed Fauzan; Nugraha, Roni (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2025)
This article examines “From Children’s Literature to Faith-Character Education: A Narrative Analysis of the Novel ‘Petualangan Si Bocah Soleh’ (Adventures of the Pious Boy).” The study aims to analyze how Roni integrates faith-character (akidah-akhlak) education values into fictional storytelling through narrative and reflective approaches. The findings reveal that the adventure narrative incorporates three theological relations between God and humans: mercy (Creator-Creation), monotheism (Worshipper-Worshipped), and divine justice (Judge-Accountable). Additionally, through faith-based adventure storytelling, the author articulates the development of noble moral/character values—such as courage, honesty, responsibility, patience, solidarity (ukhuwah), discipline, and environmental stewardship—conveyed contextually through plot dynamics and character conflicts. With its aesthetic and affective approach, Petualangan Si Boleh is positioned as an applicative, inspirational, and transformative medium for faith-character education among elementary school readers.